Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2004)
Table of Content Kiki Smith’s Logophilia by Vincent Katz 20 Years of Parkett Essay by Nicolas Bourriaud, Interview with Pipilotti Rist Closed Circuit by Anne Söll Olaf Breuning See? It is always the same story by Marc-Olivier Wahler Technician oft the Sacred by Carissa Rodriguez In Search of Lost Purpose by Gianni Jetzer Richard Phillips Out of Time and Place – A Conversation with Diedrich Diederichsen & Richard Phillips Face All Wrath! by Jutta Koether Contemporary American Sublime by Christian Rattemeyer Keith Tyson Primordial Soups by Michael Archer It`s like an organic system – A Conversation with Ethan Wagner & Keith Tyson Fabulous Art by Hans Rudolf Reust Dan Perjovschi, Insert Walterday – Walter Pfeiffer by Michelle Nicol Beyond Words – Fionna Banner by Francis McKee In Praise of Dialogue, Cumulus from Europe by Paolo Bianchi John Körmeling : The Freedom in Free Space, Cumulus from America by Wayne Baerwaldt Sexualized Torture and Breakfast Rolls by Klaus Theweleit
While Olaf Breuning and Richard Phillips acquire new insights by devoting themselves to the world of forms and aesthetic appearances as “taste analysts,” Keith Tyson, a latter-day uomo universale, strides through complex scientific universes as if he were strolling around in an amusement park. The visual forms and mental peregrinations of these three artists engage cultural borderlines where subjectivity and rationality, sensuousness and cold abstraction are remixed. This volume also features an Insert project by Dan Perjovschi. (editorial by publisher)
boek
Keywords: Breuning, Olaf; Tyson, Keith; Rist, Pipilotti; Phillips, Richard